1) "(y-2)dx-(x-y-1)dy=0"
"\\implies dy\/dx=(y-2)\/(x-y-1)"
Let "x=u+h;y=v+k"
"\\implies dx=du ; dy=dv"
"dy\/dx=[(v+k)-2]\/[(u+h)-(v+k)-1)]"
"dv\/du=[v+(k-2)]\/[u-v+(h-k-1)]"
Now;
"k-2=0" ;
"h-k-1=0"
Solving these equations;
"k=2; h=3"
"\\implies x=u+3; y=v+2"
"\\implies dv\/du= v\/(u-v)"
Let; "v\/u=z \\implies v=uz"
"\\implies dv\/du=z+u(dz\/du)"
"\\implies z+u(dz\/du)= z\/(1-z)"
"\\implies \\int (z^{-2}-z^{-1})dz=\\int du\/u"
"\\implies ln(uz)=-(1\/z)+c"
Substituting the values of "u,v, z, h, k;" we get;
"(y-2)=ke^{-[(x-3)\/(y-2)]}" (Answer)
2) "(x-4y-9)dx+(4x+y-2)dy=0"
"\\implies dy\/dx=(4y-x+9)\/(4x+y-2)"
Let "x=u+h;y=v+k"
"\\implies dx=du ; dy=dv"
"dy\/dx=[4(v+k)-(u+h)+9]\/""[4(u+h)+(v+k)-2)]"
"dv\/du=[4v-u+(4k-h+9)]\/""[4u+v+(4h+k-2)]"
Now;
"4k-h+9=0" ;
"4h+k-2=0"
Solving these equations;
"k=-2; h=1"
"\\implies x=u+1; y=v-2"
"\\implies dv\/du= (4v-u)\/(4u+v)"
"v\/u=z \\implies v=uz"
"\\implies dv\/du=z+u(dz\/du)"
"\\implies z+u(dz\/du)= (4z-1)\/(z+4)"
"\\implies \\int [(z+4)\/(z^{2}+1)]dz=-\\int du\/u"
"\\implies 1\/2(ln(u^2(z^2+1))=-tan^{-1}z+c"
Substituting the values of "u,v, z, h, k" ; we get;
"(x-1)^2+(y+2)^2=ke^{-8tan^{-1}[(y+2)\/(x-1)]}" (Answer)
Comments
Leave a comment